Here's the question you clicked on:
dmezzullo
Imagine you are teaching a fellow student how to solve: 2(x + 6) − 10 = 12 + 4(x − 1) In your own words, explain the process for solving this equation. Please include your work at each step of the process along with the final answer.
uggg ill do it 2 marrow if they dont i gtg
PEMDAS 2(x + 6) − 10 = 12 + 4(x − 1) first simplify 2x+12-10= 12+4x-4 add or subtract like terms 2x+2= 8+4x subtract 2 both sides -2 -2 ________________________________________ 2x= 6+4x subtract 4x on both sides -4x -4x ________________ -2x=6 divide -2 on both sides -2x/-2 = 6/-2 x=?